Cultural difference: analyzing its impact on the advertising translation of international universities - Syed Abdullah, Syed Nurulakla; Wang, Haihua; Abdullah, Muhammad Alif Redzuan (Academic Studies Press, 2024)
Translations into different languages and cultural adaptations are essential in the modernized global economy. The internationalization of higher education has propelled international universities into a competitive landscape where effective advertising plays a pivotal role in attracting a diverse student body. The fundamental objective of the research is to comprehensively observe how cultural differences influence the translation of advertising messages for international universities in Malaysia. The study delves into the complexities of cultural nuances, drawing insights from the theory of Hofstede's Cultural Dimension to understand the factors of power distance, avoidance of uncertainty, individualism versus collectivism, and long-term orientation. Data were gathered by a survey method utilizing convenience sampling techniques. An online survey self-administered by 278 international students was used to gather data. Using AMOS software, analysis was accomplished by implementing structural equation modeling (SEM) techniques. The outcomes indicate that individualism and communication effectiveness had a beneficial influence on the advertising translation of international universities in Malaysia. In the future, investigating the impact of emerging technologies, like machine learning and, artificial intelligence on the adaptation of advertising content to cultural differences represents an evolving area.